2023
DOI: 10.15452/cejnm.2022.13.0015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patient safety culture from the perspective of nursing students - a literature review

Abstract: Aim: To identify instruments measuring patient safety culture from the perspective of nursing students and to assess the content and reported psychometric properties of these instruments. Design: A narrative literature review. Methods: The search was carried out (according to institutional availability) in three scientific databases: ProQuest, PubMed, and Scopus. The search produced a total of 645 studies published up to May 2021. For data analysis, a summative content method was used. Results: We identified 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Supervision of clinical practice only influenced evaluation of Culture of safety in the academic setting. The impact of supervision on the evaluation of patient safety culture in the Czech environment during the Covid-19 pandemic was also reported in the study by Bartoníčková et al (2023), using a different instrument. Several international studies have indicated an impact on competence assessment with regard to experience of adverse events (e.g.…”
Section: Discussionmentioning
confidence: 60%
“…Supervision of clinical practice only influenced evaluation of Culture of safety in the academic setting. The impact of supervision on the evaluation of patient safety culture in the Czech environment during the Covid-19 pandemic was also reported in the study by Bartoníčková et al (2023), using a different instrument. Several international studies have indicated an impact on competence assessment with regard to experience of adverse events (e.g.…”
Section: Discussionmentioning
confidence: 60%